1997
DOI: 10.1038/sj.sc.3100381
|View full text |Cite
|
Sign up to set email alerts
|

Fathering of a child with the assistance of electroejaculation in conjunction with intracytoplasmic sperm injection: case report

Abstract: Ejaculatory failure and poor fertility are major problems for patients with spinal cord injury, who wish to father children. Arti®cial ejaculation in conjunction with assisted reproductive techniques has been proposed as a possible solution to this situation. In this paper, we presented the case of a tetraplegic man who fathered a child with the aid of electroejaculation with intracytoplasmic sperm injection (ICSI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…There have been relatively few reports on the use of micromanipulation procedures in the partners of SCI males. 18,44,58 Hultling et al, 20 comparing conventional IVF to an IVG/ICSI protocol, found a higher fertilisation rate after the introduction of ICSI but no di erence in the clinical pregnancy rate. They found a pregnancy rate per cycle for the IVF/ICSI protocol of 31% and a cumulative pregnancy rate per couple of 56%.…”
Section: Discussionmentioning
confidence: 99%
“…There have been relatively few reports on the use of micromanipulation procedures in the partners of SCI males. 18,44,58 Hultling et al, 20 comparing conventional IVF to an IVG/ICSI protocol, found a higher fertilisation rate after the introduction of ICSI but no di erence in the clinical pregnancy rate. They found a pregnancy rate per cycle for the IVF/ICSI protocol of 31% and a cumulative pregnancy rate per couple of 56%.…”
Section: Discussionmentioning
confidence: 99%
“…Rationale: Most men with SCI will experience some erectile and ejaculatory difficulties. As a result, assistance with fertility for biological fatherhood is often necessary (Brackett et al, 1998a, Yamamoto et al, 1997Rutkowski et al, 1999;Salsabili et al, 2006;Shieh et al, 2003, Brackett et al, 2007, Brinsden et al, 1997. For men with incomplete lesions, natural ejaculation and insemination with vaginal intercourse may be possible.…”
Section: Discuss the Prognosis For Biological Fatherhood And Options mentioning
confidence: 99%
“…We have two successful cases as yet, in one of which the sperm motility rate was almost 0% and in the other 5%. 17 Theoretically, employment of ICSI almost always enables fertilization followed by pregnancy, even if the semen contains only a few spermatozoa as is the case in some patients. The development of reproductive technologies has decreased the signi®cance of semen quality.…”
Section: Comments By Dr Momosementioning
confidence: 99%